2021
DOI: 10.3390/jcm10030429
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Surgical Treatment of Endometrial Cancer Using Traditional and Laparoscopic Methods

Abstract: Surgical treatment is the most important part of therapy for endometrial cancer. The aim of the study was to define factors having the most significant impact on surgical treatment of endometrial cancer when using traditional and laparoscopic methods. In the study, we evaluated 75 females who were treated for endometrial cancer via laparoscopic surgery in 2019 and used a historical control of 70 patients treated by laparotomy in 2011. The evaluated risk factors included the method of surgery, type of lymphaden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In addition, laparoscopic surgery is performed in a relatively closed abdominal cavity, and the pelvic and abdominal organs do not need to be exposed for a long time, and the intestinal tract will not be dry and cold, so that the patient's gastrointestinal motility function can be quickly recovered after surgery. [49][50][51] There are no significant differences in recurrence and survival between LRH and ARH. A long-term follow-up study 52 has found that the 5-year survival rate after LRH was basically the same as that of laparotomy.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In addition, laparoscopic surgery is performed in a relatively closed abdominal cavity, and the pelvic and abdominal organs do not need to be exposed for a long time, and the intestinal tract will not be dry and cold, so that the patient's gastrointestinal motility function can be quickly recovered after surgery. [49][50][51] There are no significant differences in recurrence and survival between LRH and ARH. A long-term follow-up study 52 has found that the 5-year survival rate after LRH was basically the same as that of laparotomy.…”
Section: Discussionmentioning
confidence: 92%
“…The possible reason for the difference may be that laparoscopic surgery avoids the touch of the abdominal retractor, gauze and operator’s gloves on the intestine, and the less intestinal tract manipulations in the LRH reduce irritation to the patient’s gastrointestinal tract. In addition, laparoscopic surgery is performed in a relatively closed abdominal cavity, and the pelvic and abdominal organs do not need to be exposed for a long time, and the intestinal tract will not be dry and cold, so that the patient’s gastrointestinal motility function can be quickly recovered after surgery 49–51…”
Section: Discussionmentioning
confidence: 99%